Anesthetic management in patients suspected of Creutzfeldt-Jakob disease -A case report- - In, Chi Bum (The Korean Society of Anesthesiologists, 2011)
Creutzfeldt-Jakob disease (CJD) is a fatal neurodegenerative disorder in which accumulation of the pathogenic prion protein induces neuronal damage and results in distinct pathologic features. This abnormal prion is an infectious protein and resistant to methods of sterilization currently being used. Therefore, management of definite, or suspected CJD patients requires additional precautions. We report our experience of a patient who had undergone brain biopsy for suspected of CJD. The patient was confirmed to have sporadic CJD.